2006
DOI: 10.1021/jp057342h
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Liquid Ammonia Based on the Combined Quantum Mechanical/Molecular Mechanical (QM/MM) Approach

Abstract: Two combined quantum mechanics/molecular mechanics (QM/MM) molecular dynamics simulations, namely, HF/MM and B3LYP/MM, have been performed to investigate the local structure and dynamics of liquid ammonia. The most interesting region, a sphere containing a central reference molecule and all its nearest surrounding molecules (first coordination shell), was treated by the Hartree-Fock (HF) and hybrid density functional B3LYP methods, whereas the rest of the system was described by the classical pair potentials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 40 publications
(140 reference statements)
0
29
0
Order By: Relevance
“…On the one hand, this hybrid methodology is able to provide reliable results at a reasonable computational cost and has been established as a valuable tool for modeling, not only biomolecular compounds, [14][15][16][17][18][19][20][21] but also inorganic/organometallic complexes, [22][23][24][25][26] solid state systems [27][28][29][30] and mixed solvent solutions. [31][32][33][34] On the other hand, the level of theory and the basis set influence significantly simulation trends and energy values. 35,36 In addition, the method has also been found very sensitive to the definition of the boundary between the various subsystems.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, this hybrid methodology is able to provide reliable results at a reasonable computational cost and has been established as a valuable tool for modeling, not only biomolecular compounds, [14][15][16][17][18][19][20][21] but also inorganic/organometallic complexes, [22][23][24][25][26] solid state systems [27][28][29][30] and mixed solvent solutions. [31][32][33][34] On the other hand, the level of theory and the basis set influence significantly simulation trends and energy values. 35,36 In addition, the method has also been found very sensitive to the definition of the boundary between the various subsystems.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent ONIOM-XS MD simulation of Li + in aqueous ammonia solution [13], although the MRT values for first-shell ligands are significantly higher than those of pure solvents, it has been shown that the first solvation shell of Li + is somewhat flexible and that the 'structure-making' ability of Li + is not too strong. As compared to the case of Li + , it could be demonstrated that K + acts as a clear 'structure-breaking' ion, i.e., the MRT values for ligands in the first solvation shell of K + are not much different to the corresponding values observed in the pure solvent environments [12,31]. Interestingly, the MRT data of water molecules in the first solvation shell of K + are even less than the corresponding values for water molecules in the hydration shell of K + [10].…”
Section: Resultsmentioning
confidence: 96%
“…Since in light of these results, the relative number of neighboring H atoms ͑2 out of Ïł42͒ is much smaller than in liquid H 2 O ͑4 out of 8͒, it seems plausible to argue that liquid ammonia does not belong to the group of strongly associated liquids even at low temperatures. Modern computer simulations based on Car-Parinello ab initio molecular dynamics 20 and mixed quantum/classical molecular dynamics 21 support such an assignment of liquid NH 3 to weakly associated fluids.…”
Section: Introductionmentioning
confidence: 97%